Efek Reputasi Kap dan Keterlambatan Laporan Auditor Independen Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan - Zulkifli Umar; Ermad M J; Dhea Adhima Suemdra (Jurnal EMT KITA, 2022)
This study aims to examine the effect of the reputation of the public accounting firm and the delay in the independent auditor's report on the timeliness of submitting financial statements. This research is a sample study, which includes 225 companies from 510 manufacturing sector companies during the 2017-2019 observation year. The sample was selected by simple random sampling technique, the sample size was determined by the slovin formula. The analytical method used is logistic regression. The results of the study found that the reputation of public accounting firms had an effect on increasing the timeliness of submitting financial reports, especially public accounting firms affiliated with the Big 4. The delay in the independent auditor's report also affects the timeliness of the financial report submission, especially the auditor who is not late in submitting the independent auditor's report.